Direct participation of Ukrainian militia in fight against German invaders in 1941-1945 - Тимченко, Анатолій Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article characterizes the operational situation and the war period. Much attention has been paid to timely made by bodies of state power and administration normative legal acts, which stressed that the military state required militia personnel at any time, under any circumstances would be ready to take decisive action in fight against the enemy. Also, those legislative documents gave the direct tasks to Ukrainian militia to be prepared independently or together with divisions of the Red Army for military actions to liquidate subversive groups, parachute landings, spies and active enemy’s divisions. One of many directions of militia activities in emergency conditions of war in 1941-1945 has been investigated, in particular, the direct participation of Ukrainian militia in fight against German invaders. Attributes of their activity that contributed to progressive execution of tasks in fight against the enemy and Victory over Nazi Germany have been determined.